2006
DOI: 10.3233/jad-2006-9309
|View full text |Cite
|
Sign up to set email alerts
|

Detection of biomarkers with a multiplex quantitative proteomic platform in cerebrospinal fluid of patients with neurodegenerative disorders

Abstract: Biomarkers are needed to assist in the diagnosis and medical management of various neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), and dementia with Lewy body (DLB). We have employed a multiplex quantitative proteomics method, iTRAQ (isobaric Tagging for Relative and Absolute protein Quantification), in conjunction with multidimensional chromatography, followed by tandem mass spectrometry (MS/MS), to simultaneously measure relative changes in the proteome of cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
314
6
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 362 publications
(341 citation statements)
references
References 46 publications
19
314
6
2
Order By: Relevance
“…Although the level of DBP in CSF has been known to be increased in AD patients, and several lines of evidence have suggested that DBP plays a role in AD, 11,15,16,32 there is no direct evidence of whether or how DBP affects AD-related pathology. Our data clearly show that DBP interacts directly with Ab and reduces the formation of aggregated Ab.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the level of DBP in CSF has been known to be increased in AD patients, and several lines of evidence have suggested that DBP plays a role in AD, 11,15,16,32 there is no direct evidence of whether or how DBP affects AD-related pathology. Our data clearly show that DBP interacts directly with Ab and reduces the formation of aggregated Ab.…”
Section: Discussionmentioning
confidence: 98%
“…As many Ab-binding proteins, such as TTR, apoE, apoJ, and apoA1, are known to accumulate with Ab in amyloid No Ab bands were detected in the littermate mice; n ¼ 4 each cases deposits 5,17 and the level of DBP in CSF is increased in AD patients, 11,15,16 we examined whether DBP is present in the amyloid plaques of brains from AD patients and transgenic animal model of AD. We double-stained human AD and control brain with antibodies against Ab (4G8) and DBP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10). It is also encouraging that many of the 81 proteins have already been reported as potential biomarkers for AD by multiple independent groups [2,20,28,31,36,[58][59][60][61]. Indeed, because none of these previously reported candidate biomarkers have been vetted sufficiently to be applied in clinical trials, they will have to be studied further: individually and in combination; in larger cohorts and in different diseases.…”
Section: Alternative and Evolving Strategies For Peptide Identificationmentioning
confidence: 99%